The Importance of Personality Traits, Optimism and Quality of Life for Pain Threshold and Pain Tolerance in the Elderly - Tomasz Gałkowski; Katarzyna Leźnicka; Kinga Michnik; Grzegorz Pawlus (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2023)
With increasing age, the frequency of chronic pain increases compared to acute pain. This is due to structural and functional changes caused by ageing of the nervous system. The aim of this study was to investigate relationships between personality traits, optimism, quality of life, and subjective assessment of pain measured experimentally with an algometer and clinically with the Visual Analoque Scale (VAS). In the group of 133 seniors (61-86 years; 78% women), we used an algometer to measure pain threshold and tolerance, the VAS scale to assess subjective intensity, and standardized questionnaires (EPQ-R(s), LOTR, SWLS) to measure psychological variables. Extraversion was found to promote both higher pain threshold and higher pain tolerance, whereas pain tolerance was negatively correlated with neuroticism. Higher severity of the psychotic trait was associated with more intense subjective pain experience. Optimism and overall quality of life were not associated with any pain measures. A better understanding of the personality correlates of pain perception could support a more accurate tailoring of pain management in elderly patients.